Lifetime versus annual tax progressivity: Sweden, 1968-2009 - Niklas Bengtsson; Bertil Holmlund; Daniel Waldenström (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper analyzes the evolution of tax progressivity in Sweden from both annual and lifetime perspectives. Using a rich micro panel with administrative records of incomes, taxes and benefits over the period 1968-2009, we calculate tax rates across the income distribution accounting for different tax bases as well as the role of transfers. The uniquely long time span also allows us to compute tax progressivity as realized over a cohort's entire life cycle. Our main finding is that taxes are considerably less progressive over the lifetime than in any single year. In fact, life cycle taxes are close to proportional, bearing a redistributive effect of only a few percent. Intragenerational income mobility seems to be driving this result, but the Swedish economic crisis of the 1990s and the tax reforms of 1971 and 1991 are also important events. Labor income taxes contribute less to progressivity in recent years, whereas transfers to unemployed and old-age pensioners have become increasingly important. Our findings are robust to using different tax rates, tax bases, sample populations, discount rates and re-ranking controls.
Keywords: D31; H20; 330; tax progressivity; income distribution; lifetime income; redistributive effect; Kakwani index; transfers; Steuerprogression; Sozialtransfer; Steuerinzidenz; Lebenseinkommen; Einkommensverteilung; Schätzung; Schweden